Reflections on the impact of COVID-19 in the struggle to eliminate violence against women - Rebaza Vilchez, Karen Maribel (2020)
Violence against women is a global social problem that has been aggravated by COVID-19 and government confinement orders to prevent its spread. Our country, like many in the region and the world, has been implementing public policies designed to protect women against abuse. However, due to this special context, the impact of these policies has been diminished since many women live with their aggressor, consequently, have less possibility of protection. In this context, this article aims to assess, in light of international standards on the matter, whether our internal law has been fulfilling its preventive and protective role or, on the contrary, wether requires changes or adjustmentsto guarantee its effectiveness. in pandemic.